Underexpression of LINC00173 in TCF3/PBX1-Positive Cases Is Associated With Poor Prognosis in Children With B-Cell Precursor Acute Lymphoblastic Leukemia - May-Hau, Didier Ismael; Bárcenas-López, Diego Alberto; Núñez-Enríquez, Juan Carlos; Bekker-Méndez, Vilma Carolina; Beltrán-Anaya, Fredy Omar; Jiménez-Hernández, Elva; Ortíz-Maganda, Mónica Patricia; Guerra-Castillo, Francisco Xavier; Medina-Sanson, Aurora; Flores-Lujano, Janet; Martín-Trejo, Jorge Alfonso; Peñaloza-González, José Gabriel; et al. (Frontiers in Oncology, 2022)
Background. B-cell precursor acute lymphoblastic leukemia (BCP-ALL) is the most frequent pediatric cancer worldwide. Despite improvements in treatment regimens, around 20% of the cases cannot be cure, highlighting the necessity for identifying new biomarkers to improve the current clinical and molecular risk stratification schemes. We aimed to investigate whether LINC00173 is a biomarker in ALL and to explore its expression level in other human cancer types. Methods. A nested case-control study including Mexican children with BCP-ALL was conducted. LINC00173 expression was evaluated by qRT-PCR using hydrolysis probes. To validate our findings, RNA-seq expression data from BCP-ALL and normal tissues were retrieved from TARGET and Genotype-Tissue Expression (GTEx) repositories, respectively. LINC00173 expression was also evaluated in solid tumors by downloading available data from The Cancer Genome Atlas (TCGA). Results. A lower expression of LINC00173 in BCP-ALL cases compared to normal subjects was observed (P < 0.05). ALL patients who carrier the TCF3/PBX1 fusion gene displayed lower expression of LINC00173 in contrast to other BCP-ALL molecular subtypes (p<0.04). LINC00173 underexpression was associated with a high risk to relapse (HR = 1.946, 95% IC = 1.213-3.120) and die (HR = 2.073, 95% IC = 1.211-3.547). Patients with TCF3/PBX1 and underexpression of LINC00173 had the worst prognosis (DFS: HR = 12.24, 95% IC = 5-0.4-29.71; OS: HR = 11.19, 95% IC = 26-32). TCGA data analysis revealed that underexpression of LINC00173 is also associated with poor clinical outcomes in six new reported tumor types. Conclusion. Our findings suggest that LINC00173 is a biomarker of poor prognosis in BCP-ALL and other types of cancer. We observed an association between the expression of LINC00173 and TCF3/PBX1 and the risk to relapse and die in BCP-ALL, which is worse in TCF3/PBX1 positive cases displaying underexpression of LINC00173. Experimental studies are needed to provide insight into the LINC00173 and TCF3/PBX relationship.